Antioxidant and cytoprotective properties of partridgeberry polyphenols. (1st February 2015) - Bhullar, Khushwant S.; Rupasinghe, H.P. Vasantha
Highlights: A solvent system for greatest polyphenol recovery from partridgeberry was identified. A process for preparation of polyphenol sub-classes-rich fractions was established. Phenolic concentrations of fractions were measured using UPLC–ESI–MS/MS. The polyphenol-rich fractions exhibited cytoprotection in human lung fibroblasts. The Nrf2 pathway was activated by the polyphenol-rich fractions of partridgeberry. Abstract: Partridgeberry ( Vaccinium vitis-idaea ) is a polyphenol-rich berry of the Ericaceous family, grown in Newfoundland and Labrador province of Canada. The aims of this study were to identify extraction solvents for the maximum recovery of polyphenols, to establish fractionation technique for isolation of major sub-classes of polyphenols, and to evaluate antioxidant and cytoprotective properties of the partridgeberry polyphenol preparations. The acidified 70% acetone was identified as the ideal solvent for the maximum recovery of polyphenols from partridgeberry. Further, aqueous two-phase extraction, column chromatography and UPLC–MS/MS were employed to produce three partridgeberry polyphenol fractions, rich in either, anthocyanins, flavan-3-ols or flavonols. All the three PPF were potent antioxidants and displayed cytoprotective activity through the activation of nuclear factor erythroid 2-related factor 2 pathway, scavenging of reactive oxygen species, and inhibition of cellular death. The current study suggests that partridgeberry has numerous potential health implications in both prevention and amelioration of various diseases involving oxidative stress.